Testing information security management system tool v2.1.1.0 based on ISO 27001:2005 - Shehu, Abdulrahman Mustafa (2012)
Every single day software engineers are born with new talented skills and logics. They all engage in developing sophisticated systems that will affect the life of the intended users in either positive or negative ways. It was also surprising to know that recently even a 13year old Pakistani was able to break the record of been the youngest Microsoft certified professional (MCP). Some are saying that doctors are more important to the society than all other professional bodies but the way the world is moving we can say software engineers can have equal or even more importance to the world today. Having this entire competitive platform in our mist, it is very important to give maximum effort and consideration to the testing of developed systems. Although engineers at large cannot test their products to a point of saturation, they will try to make it by anticipating situations where it might possibly fail, producing dedicated verification and validation terms and other different ways. Usually, the time allocated to testing activities is limited as the producers are eager to send the product to the client side and collect the remaining contract balance. This report aimed at exploring the concept of information security management system (ISMS) and the tool used to automate the implementation of ISMS by monitoring organisation’s ISMS compliance. A complete standard was provided to guide in the requirements to implement ISMS which is ISO 27001. The standard envelope the establishment, implementation, operation, monitoring, review, maintenance and improvement of ISMS. This states how vital it is to conduct thorough testing on the tool to ensure an error free system is used to manage the delicate task of managing important information. The report highlights all the testing activities carried out on the delicate tool to regain its standability and strength.